Tracing bloodlines: Kinship and reproduction under investigation in CSI: Crime Scene Investigation - Bull, Sofia (Journal of Popular Television, The, 2014)
Abstract This article examines discourses on kinship and reproduction in the forensic crime drama CSI: Crime Scene Investigation (2000–). I argue that the programme stages a visual materialization of genetic kinship in order to assert its importance as a crucial type of forensic evidence, which evokes the traditional Darwinian framework of genealogy for understanding biological kinship as a substantial and enduring trace between generations. However, I show that CSI also participates in contemporary bioethical debates about new genetic and biomedical technologies that increasingly allow us to interfere in the human reproduction process. The programme engages with an emergent post-genomic re-spatialization of genealogy and acknowledges that the concept of kinship is increasingly being redefined, but it is still heavily invested in a normative understanding of sexual reproduction as a ‘natural fact of life’ and inadvertently constructs the nuclear family structure as an ideal framework for procreation.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9qcHR2LjIuMi4xMTdfMQ